Spelling Compliance and Institutional Professionalism: A Sociolinguistic Analysis of Official Documents in Indonesian Local Government - Huplan Huplan; Yessi Fitriani; Puspa Indah Utami (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines compliance with the General Guidelines for Indonesian Spelling (PUEBI) in official documents from the Palembang City Education Office and analyzes the sociolinguistic implications of spelling errors for institutional professionalism. Using qualitative content analysis of 20 official documents (official letters, memos, circulars, and activity reports) and semi-structured interviews with document preparers, we identified 152 spelling violations across six error categories. Word writing errors (28%), non-standard loanwords (17%), and punctuation mistakes (15%) were most prevalent. Critically, we documented serious errors including misspelled city names (